Investigation of physicochemical condition to stabilize phosphatidylcholineliposome enclosing fluorescent calcein and its exploitation for analysis of pore formation with Cry1A toxins of Bacillus thuringiensis - Kohsuke Haginoya (2018)
Liposome was prepared using phosphatidylcholine (PC), and calcein, a fluorescent chemical, was simultaneously enclosed within the liposome (PC-Lipo). The stability of PC-Lipo in its ability to retain calcein was evaluated under various conditions. PC-Lipo lost stability at pH 6 and pH 11-13, but was stable in the range of pH 8.3-10. PC-Lipo was stable in the temperature range of 15-30°C, but lost the stability acutely at 35°C. Ionic strength, given as the concentration of NaCl, also affects its stability, and a higher concentration of NaCl, i.e., more than 150mM, induced a higher leak of calcein from PC-Lipo. The optimal conditions to achieve stable PC-Lipo were employed to characterize the differences in pore formation with Bacillus thuringiensis Cry1Aa, Cry1Ab and Cry1Ac toxins. These toxins were reacted with PC-Lipo under these optimal conditions, and the affinity and maximum speed of Cry1Ab to form pores on PC-Lipo was shown to be highest. Here we show these conditions and evidence of the usefulness of PC-Lipo to investigate the mode of action of Cry1A toxins.